30.0k views
4 votes
−3(6x + 2) simplify

User Protheus
by
5.3k points

2 Answers

3 votes
-3(6x+2)
-3x6x=-18x
-18x
-3x2=-6
-18x-6
I may be wrong
User DiscoveryOV
by
5.1k points
3 votes

Hey!

------------------------------------------------

To simplify the equation we can use distributive property.

−3(6x + 2) → (-3 * 6x) + (-3 * 2) → -18x - 6

------------------------------------------------

Hence, the answer is
\Large\boxed{\mathsf{-18x~-~6}}

------------------------------------------------

Hope This Helped! Good Luck!

User SioGabx
by
5.5k points